OPTIMASI PENGUKURAN LAJU AIR PADA SUSUNAN PERALATAN EKSPERIMEN DINAMIKA FLUIDA SEDERHANA - I Gede Rasagama (UNIVERSITAS MUHAMMADIYAH METRO, 2020)
The research objective is to determine the results of optimization of water rate measurements in the arrangement of simple fluid dynamics experimental equipment. The study used an experimental method based on 5 theoretical equations. The research shows that the optimization of measurements can only be done on the study of changes in water surface position, differences in diameter pairs, differences in the diameter of the second pipe, and differences in pump conditions. The results of water rate measurements for references 0, 1, and 2, respectively, have a specific tendency for the study of changes in physical quantities and, or differences in the associated physical conditions. The mean coefficient of determination by the surface height to the reference rate of 0 is 58%, with respect to the reference rates 1 and 2, respectively 76% and 73%. By the difference in diameter with reference rate 2 based on equations (3) and (5), they are 94% and 74%, respectively.